(untitled) - Sedliak, Marian; Sulgan, Marian (Doprava a spoje, 2010)
This paper brings information about the supplier - customer relationships in the automotive manufacturers, and how outsourcing of logistics activity may contribute to the higher achievement the inbound logistical objectives.